Fashion, artificial intelligence, and representation: the aesthetic and symbolic construction of the Dreamy Winter Escape campaign – Farm Rio Global (ModaPalavra e-periódico, 2026)
This article aimed to analyze the symbolic and aesthetic construction of the Dreamy Winter Escape campaign by Farm Rio Global, focusing on the integration of artificial intelligence (AI) as a creative tool in fashion visualities. To this end, it adopts a basic, qualitative, and descriptive research approach, using bibliographic and documentary surveys as technical procedures. The analysis reveals that although the campaign presents visual innovations through the use of AI, it reproduces Eurocentric beauty standards and exoticizes Brazilian tropicality, disregarding the country’s ethno-racial diversity. The results indicate that the uncritical use of AI reinforces hegemonic aesthetics and automates historical exclusions instead of subverting representational paradigms. Thus, the study highlights the need for an aesthetic-political commitment to the use of emerging technologies in order to promote plural and inclusive representations in digital fashion.
Keywords: artificial intelligence; farm rio; digital fashion; representation